Pelatihan Mindfulness pada Guru PAUD ANANDA di RW 19 Sendangmulyo-Semarang - Rusmalia Dewi; Gusti Yuli Asih; Yudi Kurniawan; Agung Santoso Pribadi (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this community service (PkM) is to provide Mindfulness training to ANANDA PAUD teachers in RW.19 to improve their understanding of themselves regarding their physical and psychological well-being. Mindfulness training is a meditation method used to increase empathy both affectively, cognitively, morally, intrapersonally and interpersonally. The many activities and activities of teachers both at school and at home make teachers feel very tired. Teachers often feel dizzy, physically tired and lack focus on the teaching given. To prevent these things from continuing, the PkM team of the psychology faculty provides assistance to teachers by holding Mindfulness training which aims to maintain the mental state of teachers from the pressures that arise both at work and brought from home. The lack of understanding and self-skills possessed by the teachers makes them just resigned in carrying out their daily activities. This input prompted the PkM team to help find solutions for developing the self-skills of ANANDA PAUD teachers through Mindfulness Training. The process involved gathering the teachers in the RT.01 hall and providing them with materials to understand and practice Mindfulness, including lectures, stories, and practical exercises, as well as games and group discussions. The community service team hopes that these teachers will be able to understand the results of the training. This increased understanding of Mindfulness will improve their ability to focus and better understand themselves and their surroundings, enabling them to overcome all the challenges and obstacles that arise in their daily lives.